The Adaptability of Teachers in My Home Kindergarten Grows in the Context of Competency Development to Face the Era of Smart Society 5.0 - Abidin, Muhammad Zainal; Purwandari, Septiyati (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2023)
This research aims to outline the strategies of teachers at Rumahku Tinggi Kindergarten in facing the Era 5.0. Era 5.0 is marked by teacher abilities which include the 4c's, namely creativity, critical thinking, communication, collaboration. In theory, one of the efforts to face the challenges of the 5.0 revolution is that teachers need to carry out self-management, social aspects of human and machine relations, practical innovation of smart learning, and skills upgrading. This research uses qualitative research methods, with the population and research sample covering all activities in the school as well as the principal, curriculum area and class teachers as the research sample. Data collection uses interview, observation and documentation techniques. Research analysis goes through several stages, namely data collection, data reduction, data display, and conclusion drawing/verification. The research results show that first the teachers carry out self-management from the beginning of learning to the end of the activity. Second, adaptability carried out by teachers is skill upgrading, which is carried out by further study, attending various types of training that supports improving the quality of training and conducting regular evaluations or work meetings. Third, namely practical innovation of smart learning. Teachers carry out practical innovation of smart learning in the form of applying the read aloud method to reading activities with children. The fourth adaptability is social aspects of human and machine relations. This form of adaptability cannot yet be implemented optimally due to limited technological facilities.Keyword : Competencies, Teachers, Challenges, Era 5.0.Penelitian ini bertujuan untuk menguraikan strategi guru-guru di TK Rumahku Tinggi dalam menghadapi Era 5.0. Era 5.0 ditandai dengan kemampuan guru yang meliputi 4c, yaitu kreativitas, berpikir kritis, komunikasi, kolaborasi. Secara teori, salah satu upaya untuk menghadapi tantangan revolusi 5.0 adalah guru perlu melakukan manajemen diri, aspek sosial hubungan manusia dan mesin, inovasi praktis pembelajaran cerdas, dan peningkatan keterampilan. Penelitian ini menggunakan metode penelitian kualitatif, dengan populasi dan sampel penelitian meliputi seluruh kegiatan di sekolah serta kepala sekolah, bidang kurikulum dan guru kelas sebagai sampel penelitian. Pengumpulan data menggunakan teknik wawancara, observasi dan dokumentasi. Analisis penelitian melalui beberapa tahap, yaitu pengumpulan data, reduksi data, tampilan data, dan penarikan kesimpulan/verifikasi. Hasil penelitian menunjukkan bahwa pertama-tama guru melakukan manajemen diri dari awal pembelajaran hingga akhir kegiatan. Kedua, kemampuan beradaptasi yang dilakukan guru adalah peningkatan keterampilan, yang dilakukan dengan studi lanjut, mengikuti berbagai jenis pelatihan yang mendukung peningkatan kualitas pelatihan dan melakukan evaluasi atau rapat kerja secara berkala. Ketiga, yaitu inovasi praktis smart learning. Guru melakukan inovasi praktis smart learning berupa penerapan metode read aloud pada kegiatan membaca bersama anak. Kemampuan beradaptasi keempat adalah aspek sosial dari hubungan manusia dan mesin. Bentuk kemampuan beradaptasi ini belum dapat diimplementasikan secara optimal karena keterbatasan fasilitas teknologi.